Standarisasi Ekstrak Etanol 96% Bulu Babi Echinometra Mathaei Dari Perairan Bangkalan - Kresnamurti, Angelica; Izazi, Farizah; kurniawati, dwi (Universitas Muhammadiyah Gresik, 2020)
Echinometra mathaei sea urchins are known to contain chemical compounds that can be used to overcome health problems, one of which has antioxidant activity. Some previous studies have explained the benefits of sea urchins but to ensure the quality assurance of sea urchins extracts, efforts should be made to determine the quality standards of sea urchins extract. This study aims to standardize specific parameters and non-specific parameters on Echinometra mathaei sea urchins extract to ensure the quality of 96% ethanol extract. Samples were obtained from Rongkang Beach, Kwanyar District, Bangkalan District, Madura which were then extracted using maceration method with 96% ethanol solvent. The results of the study for specific parameters showed that organoleptically and macroscopically the extracts were thick, blackish brown in color and characteristic of sea urchins; levels of dissolved compounds in ethanol of 78.37%; levels of dissolved compounds in water of 93.09%; and chemical content tests showed that the extract contained steroid compounds, tannins, flavonoids, saponins, alkaloids and terpenoids. Determination of non-specific parameters showed that Echinometra mathaei sea urchin extract had a drying shrinkage of 3.03%; specific gravity of 0.8411 g/mL; water content of 5.32%; Pb heavy metal contamination was 7.28 mg/kg, Cd was <0.0024 mg/kg, Hg was <0.0002 mg / kg, Mg was 347.83 mg / kg; microbial contamination of <10 colonies / mL; and yeast mold contamination of <10 colonies/mL. The conclusion is Echinometra mathaei sea urchin extract has the potential to be developed into a medicinal preparation. Key word: Echinometra mathaei, Specific standardize parameters, non-specific standardize parameters, Extract thanol 96%.